Chiết tách một số chất thuộc nhóm phenolic từ quả cây dứa dại Pandanus odoratissimus L. f - Cường, Nguyễn Mạnh; Sơn, Ninh Thế; Vân, Đoàn Thị; Thùy Trâm, Nguyễn Công; Thảo, Đỗ Thị; Sự, Phạm Quốc; Thuần, Nguyễn Duy (Vietnam Journal of Chemistry, 2015)
The methanol extract of fruits of Pandanus odoratissimus L. f. was partitioned in increasing polarity of organic solvents: n-hexane, chloroform and ethyl acetate. From the CHCl3 extract, four phenolic compounds, including vanillin (1), and three lignan compounds, (+)-pinoresinol (2); (+)-syringaresinol (3); and (+)-medioresinol were isolated. Their structures were determined on the basis of analysis of spectral data, including 1D-, 2D-NMR and ESI-MS.